(untitled) (Circe de clásicos y modernos, 2023)
The aim of this article is to analyze the means by which a sense of community is created in the Iliad, while focusing on the importance of action conducive to configuration of a collective identity throughout the Iliadic plot. I will to this end approach passages featuring the poet’s concern about the way a political and social community is shaped, a recurring concern which structures the action in the poem. My hypothesis is that there is a clear intention on the part of the poet to approach the problem of community identity shaping, thus reconfiguring the individualistic perspective characteristic of traditional heroic epic, towards collective forms of action.